2004
DOI: 10.1158/0008-5472.can-04-1520
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of ATR Leads to Increased Sensitivity to Hypoxia/Reoxygenation

Abstract: The transient opening and closing of tumor vasculature result in periods of severe oxygen deprivation (hypoxia) followed by reoxygenation. This exerts a positive selective pressure for cells that have lost their sensitivity to killing by reduced oxygen levels. These cells are effectively resistant to hypoxia-induced apoptosis and conventional therapeutic approaches. Here we show hypoxia-induced S-phase arrest results in regions of single-stranded DNA in stalled replication forks and signals the activation of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
86
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(93 citation statements)
references
References 38 publications
7
86
0
Order By: Relevance
“…Unlike conventional G1-phase cell cycle control, which is linked to cell differentiation, this S-phase mechanism may provide a way to control proliferation independently of differentiation in the stem cells. Induction of the PIKK/H2AX pathway seems to be independent of DNA damage, in a similar manner to that previously described during sex chromosome inactivation 14 , hypoxia 15 and mitosis 16,17 . We find it intriguing that ES and NCS cells share a similar mechanism regulating their proliferation, especially in view of the reported effects of GABA on the proliferation of adult brain progenitor cells that are positive for glial fibrillary acidic protein 18 .…”
supporting
confidence: 83%
“…Unlike conventional G1-phase cell cycle control, which is linked to cell differentiation, this S-phase mechanism may provide a way to control proliferation independently of differentiation in the stem cells. Induction of the PIKK/H2AX pathway seems to be independent of DNA damage, in a similar manner to that previously described during sex chromosome inactivation 14 , hypoxia 15 and mitosis 16,17 . We find it intriguing that ES and NCS cells share a similar mechanism regulating their proliferation, especially in view of the reported effects of GABA on the proliferation of adult brain progenitor cells that are positive for glial fibrillary acidic protein 18 .…”
supporting
confidence: 83%
“…32 Using BrdU or 3 H-thymidine incorporation assays we have been unable to demonstrate a role for Chk1 in the cell cycle response to hypoxia. 33 The DNA fiber technique demonstrated that both fork stalling and inhibition of origin firing occurred with normal kinetics in the response to hypoxia in the presence of a Chk1 inhibitor. This was somewhat surprising as we have shown previously that ATR phosphorylates Chk1 in response to hypoxia at serines 345 and 317 implying that it is active.…”
Section: Chk1 Signalling In Hypoxia/reoxygenationmentioning
confidence: 99%
“…This was somewhat surprising as it has been demonstrated that ATR, through Chk1 signalling, acts to protect stalled replication forks collapse and that this is also likely in hypoxic conditions as loss of ATR was shown to lead to accumulation of S phase specific DNA damage. 33 Our hypothesis is that loss of Chk1 during hypoxia would lead to replication fork collapse and hence model assumed a constant level of ssDNA (single stranded DNA). However, in light of the transient response of Chk1 we revisited this and quantified both ssDNA and RPA foci in hypoxia over time.…”
Section: Chk1 Signalling In Hypoxia/reoxygenationmentioning
confidence: 99%
“…This hypoxia-induced DDR includes both ATR and ATM-mediated signaling [9]. Loss or inhibition of components of the DDR, such as ataxia telangiectasia-and rad3-related (ATR) or checkpoint kinase 1 (Chk1) has been reported to sensitize hypoxic cells [10].…”
Section: Introductionmentioning
confidence: 99%